TAX POLICY ON DIGITAL FINANCIAL SERVICES: REGULATORY ANALYSIS AND ITS IMPACT ON THE FINTECH ECOSYSTEM IN INDONESIA - Dwi Koerniawati; Al-Amin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to analyse the tax policies applied to digital financial services in Indonesia and their impact on the rapidly growing fintech ecosystem. Digital financial services have brought about significant transformations in financial inclusion and innovation, but they have also created new tax regulatory challenges that the government must adapt to. This study uses a qualitative approach with literature analysis. The results of the analysis show that although digital tax policies have succeeded in providing legal certainty and increasing state revenue, these policies also have an impact on increasing fintech operational costs, which affects innovation and financial inclusion. Therefore, balanced and adaptive policies are needed to support the sustainable growth of the fintech ecosystem and optimise fiscal contributions to the state.